"I don't want to be a burden" A qualitative study of the beliefs of women with chronic low back pain in relation to their painful experience. (June 2022) - Horment-Lara, Giselle; Lüttges-Sciaccaluga, Camila; Espinoza-Ordóñez, César; Aliaga-Castillo, Verónica
Abstract: Background: Women's pain is still poorly understood. Moreover, maladaptive pain beliefs contribute to the disability associated with low back pain and play a key role in the transition from acute to chronic symptoms. Objectives: To explore the beliefs of women with non-specific chronic low back pain in terms of nature of symptoms, fears associated with pain, expectations for recovery, family, social and work-related limitations, and perceived self-efficacy. Design and methods: A qualitative study with an interpretative approach was undertaken. Face-to-face, semi-structured individual interviews were performed. Study participants were 10 women with non-specific chronic low back pain living in the Metropolitan Region of Chile. Thematic analysis was used to analyze the data. A deductive process was used to code the text and categorize the data. Results: Participants described maladaptive beliefs about pain, leading to fearful attitudes and low expectations for recovery. These beliefs seemed to perpetuate pain and limit engagement in daily tasks and meaningful activities. Some of these beliefs were associated with information provided by healthcare professions. Despite having maladaptive beliefs, women perceived themselves as self-effective. Conclusion: Women with chronic low back pain described a range of different pain beliefs across a complex categorial structure. The contents of such structure may interfere with their decisions about therapeutic options. Their beliefs were often ungrounded in scientific principles, even if the information may have been provided by healthcare providers. Physical therapists would benefit from these findings to improve communication with their patients and assess the role of beliefs in decision-making. Highlights: Common maladaptive pain beliefs provoke fear and low expectations of recovery. These beliefs often arose from information from health care providers. These beliefs limit participation in daily life and meaningful roles. Despite having maladaptive beliefs, women perceived themselves as self-effective. It is recommended that physical therapists educate their patients about the multidimensionality of pain.